Polymorphism in the Promoter Region of the IL18 Gene and the Association With Severity on Paracoccidioidomycosis - Sato, Paula Keiko; Busser, Felipe Delatorre; Carvalho, Flávia Mendes da Cunha; Gomes dos Santos, Alexandra; Sadahiro, Aya; Diogo, Constancia Lima; Kono, Adriana Satie Gonçalves; Moretti, Maria Luiza; Luiz, Olinda do Carmo; Shikanai-Yasuda, Maria Aparecida (Frontiers in Immunology, 2020)
Paracoccidioidomycosis is an important endemic systemic disease in Latin America, caused by Paracoccidioides spp. This mycosis has been associated with high morbidity and sequels, and its clinical manifestations depend on the virulence of the infecting strain, the degree and type of immune response, infected tissues, and intrinsic characteristics of the host. The Th(T helper)1 and Th17/Th22 cells were related with resistance and control of the infection, while a Th2/Th9 response was associated with disease susceptibility. In this study, we focus on interleukin (IL)-12p35 (IL12A) and IL-18 (IL18) and IFN-γ Receptor 1 (IFNGR1) genetic polymorphisms, since their respective roles have been described in human paracoccidioidomycosis. Real Time PCR was employed to analyze IL12A -504 G/T (rs2243115), IL18 -607 C/A (rs1946518) and IFNGR1 -611 A/G (rs1327474) Single Nucleotide Polymorphisms (SNP). One-hundred and forty-nine (149) Acute Form (AF), Multifocal Chronic (MC) or Unifocal Chronic (UC) forms of PCM, and 110 non-PCM individuals, as a control group were included. In the unconditional logistic regression analysis adjusted by ethnicity and sex, we observed high risk of the IL18 -607 A-allele for both AF [p= 0.015; OR= 3.10 (95% CI: 1.24 - 7.77)] and MC groups [p= 0.023; OR= 2.61 (95% CI: 1.14 - 5.96)] when compared with UC. The IL18 -607 A-allele associated risk for AF and MC groups as well as the protective role of the C-allele in UC are possibly linked to higher levels of IL-18 at different periods of the course of the disease. Therefore, a novel role of IL18 -607 C/A SNP was shown in the present study, highlighting its importance in the outcome of paracoccidioidomycosis.